2017
DOI: 10.1164/rccm.201708-1629ci
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Research in ARDS.Vt Selection in Acute Respiratory Distress Syndrome

Abstract: Mechanical ventilation (MV) is critical in the management of many patients with acute respiratory distress syndrome (ARDS). However, MV can also cause ventilator-induced lung injury (VILI). The selection of an appropriate Vt is an essential part of a lung-protective MV strategy. Since the publication of a large randomized clinical trial demonstrating the benefit of lower Vts, the use of Vts of 6 ml/kg predicted body weight (based on sex and height) has been recommended in clinical practice guidelines. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 67 publications
1
49
0
1
Order By: Relevance
“…Adverse events occurred in the first 24 h of ECCO 2 R in 26 patients ( Table 3). Duration of invasive mechanical ventilation was 17 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] days. A total of 69 patients (73%) were alive at day 28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events occurred in the first 24 h of ECCO 2 R in 26 patients ( Table 3). Duration of invasive mechanical ventilation was 17 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] days. A total of 69 patients (73%) were alive at day 28.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data have demonstrated that there is no safe upper limit for P PLAT or ΔP [13,23]. For example, the mortality rate in ARDS patients with ΔP values ≤ 14 cmH 2 O is still as high as 20% [13,23]. Patient outcomes may therefore be improved by aggressively lowering ventilatory variables such as V T , P PLAT , or ΔP as facilitated by ECCO 2 R devices that remove CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a weak but significant correlation between MAPhf and optimal VThf levels in this study may indicate the need for higher VThf levels in infants with more severe lung disease or inadequate lung recruitment. Patients who responded well to recruitment probably needed lower MAPhf and VThf levels due to decreased physiologic dead space and shunt, similar to ARDS patients (23). However, there is no strong evidence to support this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Tidal volumes and PEEP are potentially modifiable factors in the management of patients with ARDS. [42][43][44][45] In accordance with the observational study design, no recommendations regarding ventilator settings were given to investigators, and mean tidal volumes around 8 ml/kg predicted body weight used in this study were higher than the 6 ml/kg usually recommended. 42,46 Modes of ventilation allowing spontaneous breathing were used for more than 40% of patients on the day of ARDS onset.…”
Section: Patients' Initial Characteristics Severity and Ventilationmentioning
confidence: 99%